A human periodontal ligament fibroblast cell line as a new model to study periodontal stress - Weider, Matthias; Schröder, Agnes; Docheva, Denitsa; Rodrian, Gabriele; Enderle, Isabel; Seidel, Corinna Lesley; Andreev, Darja; Wegner, Michael; Bozec, Aline; Deschner, James; Kirschneck, Christian; Proff, Peter; et al. (International Journal of Molecular Sciences, 2020)
The periodontal ligament (PDL) is exposed to different kinds of mechanical stresses such as bite force or orthodontic tooth movement. A simple and efficient model to study molecular responses to mechanical stress is the application of compressive force onto primary human periodontal ligament fibroblasts via glass disks. Yet, this model suffers from the need for primary cells from human donors which have a limited proliferative capacity. Here we show that an immortalized cell line, PDL-hTERT, derived from primary human periodontal ligament fibroblasts exhibits characteristic responses to glass disk-mediated compressive force resembling those of primary cells. These responses include induction and secretion of pro-inflammatory markers, changes in expression of extracellular matrix-reorganizing genes and induction of genes related to angiogenesis, osteoblastogenesis and osteoclastogenesis. The fact that PDL-hTERT cells can easily be transfected broadens their usefulness, as molecular gain- and loss-of-function studies become feasible.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Bone remodeling; Cell culture techniques; Mechanical loading; Orthodontic tooth movement

Analysis of the human SOX10 mutation Q377X in mice and its implications for genotype-phenotype correlation in SOX10-related human disease. - Truch, Kathrin; Arter, Juliane; Turnescu, Tanja; Weider, Matthias; Hartwig, Anna; Tamm, Ernst R.; Sock, Elisabeth; Wegner, Michael (Human Molecular Genetics, 2018)
UnivIS-Import:2018-09-11:Pub.2018.med.IB.LPCIPDBI.analys

Brg1-dependent chromatin remodelling is not essentially required during oligodendroglial differentiation - Bischof, Melanie; Weider, Matthias; Küspert, Melanie; Nave, Klaus-Armin; Wegner, Michael (The Journal of Neuroscience, 2015)
Myelinating Schwann cells in the vertebrate peripheral nervous system rely on Brg1 (Smarca4) for terminal differentiation. Brg1 serves as central ATP-hydrolyzing subunit of the chromatin remodelling BAF complexes and is recruited during myelination as part of these complexes by the transcription factor Sox10 in Schwann cells. Here, we analyzed the role of Brg1 during development of myelinating oligodendrocytes in the CNS of the mouse. Following Brg1 deletion in oligodendrocyte precursors, these cells showed normal survival, proliferation, and migration. A mild but significant reduction in the number of oligodendrocytes with myelin gene expression in the absence of Brg1 points to a contribution to oligodendroglial differentiation but also shows that the role of Brg1 is much less prominent than during Schwann cell differentiation. Additionally, we failed to obtain evidence for a genetic interaction between Brg1 and Sox10 comparable with the one in Schwann cells. This argues that similarities exist between the regulatory networks and mechanisms in both types of myelinating glia but that the exact mode of action and the relevance of functional interactions differ, pointing to a surprising degree of variability in the control of myelination.
EVALuna2:4972

BRG1 interacts with SOX10 to establish the melanocyte lineage and to promote differentiation. - Marathe, Himangi G.; Watkins-Chow, Dawn E.; Weider, Matthias; Hoffmann, Alana; Trivedi, Archit; Aras, Shweta; Mehta, Gaurav; Basuroy, Tupa; Mehrotra, Aanchal; Bennett, Dorothy C.; Wegner, Michael; Pavan, William J.; et al. (Nucleic Acids Research, 2017)
Mutations in SOX10 cause neurocristopathies which display varying degrees of hypopigmentation. Using a sensitized mutagenesis screen, we identified Smarca4 as a modifier gene that exacerbates the phenotypic severity ofSox10 haplo-insufficientmice. Conditional deletion of Smarca4 in SOX10 expressing cells resulted in reduced numbers of cranial and ventral trunk melanoblasts. To define the requirement for the Smarca4 -encoded BRG1 subunit of the SWI/SNF chromatin remodeling complex, we employed in vitro models of melanocyte differentiation in which induction of melanocyte-specific gene expression is closely linked to chromatin alterations. We found that BRG1 was required for expression of Dct, Tyrp1 and Tyr, genes that are regulated by SOX10 and MITF and for chromatin remodeling at distal and proximal regulatory sites. SOX10 was found to physically interact with BRG1 in differentiating melanocytes and binding of SOX10 to the Tyrp1 distal enhancer temporally coincided with recruitment of BRG1. Our data show that SOX10 cooperates with MITF to facilitate BRG1 binding to distal enhancers of melanocyte-specific genes. Thus, BRG1 is a SOX10 co-activator, required to establish the melanocyte lineage and promote expression of genes important for melanocyte function.
EVALuna2:33480

Chromatin remodelling factor Brg1 is required for Schwann cell differentiation and myelination. - Weider, Matthias; Küspert, Melanie; Bischof, Melanie; Müller, Jana; Hillgärtner, Simone; Wegner, Michael; et al. (Developmental Cell, 2012)
Schwann cells produce myelin sheaths and thereby permit rapid saltatory conductance in the vertebrate peripheral nervous system. Their stepwise differentiation from neural crest cells is driven by a defined set of transcription factors. How this is linked to chromatin changes is not well understood. Here we show that the glial transcription factor Sox10 functions in Schwann cells by recruiting Brg1-containing chromatin-remodeling complexes via Baf60a to regulatory regions of Oct6 and Krox20 genes. It thereby stimulates expression of these transcriptional regulators that then cooperate with Sox10 to convert immature into myelinating Schwann cells. The functional interaction between Sox10 and Brg1 is evident from gain- and loss-of-function studies, similar neuropathies in the corresponding mouse mutants, and an aggravated neuropathy in compound mutants. Our results demonstrate that the transcription factor-mediated recruitment of the chromatin-remodeling machinery to specific genomic loci is an essential driving force for Schwann cell differentiation and myelination. © 2012 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2012.med.IB.LPCIPDBI.chroma

Defining metaniches in the oral cavity according to their microbial composition and cytokine profile - Seidel, Corinna Lesley; Gerlach, Roman; Wiedemann, Patrick; Weider, Matthias; Rodrian, Gabriele; Hader, Michael; Frey, Benjamin; Gaipl, Udo; Bozec, Aline; Cieplik, Fabian; Kirschneck, Christian; Bogdan, Christian; et al. (International Journal of Molecular Sciences, 2020)
The human oral microbiota consists of over 700 widespread taxa colonizing the oral cavity in several anatomically diverse oral niches. Lately, sequencing of the 16S rRNA genes has become an acknowledged, culture-independent method to characterize the oral microbiota. However, only a small amount of data are available concerning microbial differences between oral niches in periodontal health and disease. In the context of periodontitis, the cytokine expression in the gingival crevicular fluid has been studied in detail, whereas little is known about the cytokine profile in hard and soft tissue biofilms. In order to characterize oral niches in periodontal health, the oral microbiota and cytokine pattern were analyzed at seven different sites (plaque (P), gingival crevicular fluid (GCF), saliva (S), tongue (T), hard palate (HP), cheek (C) and sublingual area (U)) of 20 young adults using next-generation sequencing and multiplex immunoassays. Site-specific microbial compositions were detected, which clustered into three distinct metaniches (“P-GCF”, “S-T-HP” and “C-U”) and were associated with niche-/metaniche-specific cytokine profiles. Our findings allow the definition of distinct metaniches according to their microbial composition, partly reflected by their cytokine profile, and provide new insights into microenvironmental similarities between anatomical diverse oral niches.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Cytokine profile; Metaniches; Multiplex immunoassay; Next-generation sequencing; Oral biofilms and fluids; Oral microbiota; Oral niches

Desert Hedgehog links transcription factor Sox10 to perineurial development. - Küspert, Melanie; Weider, Matthias; Müller, Jana; Wegner, Michael; et al. (Journal of Neuroscience, 2012)
Schwann cells are the main glial cell type in the PNS. They develop along nerves during embryogenesis and rely on theHMGdomain containing Sox10 transcription factor for specification, lineage progression, and terminal differentiation. Sox10 deletion in immature Schwann cells caused peripheral nerve defects in mice that were not restricted to this glial cell type, although expression in the nerve and gene loss were. Formation of the perineurium as the protecting sheath was, for instance, heavily compromised. This resembled the defect observed after loss of Desert hedgehog (Dhh) in mice. Here we show that Sox10 activates Dhh expression in Schwann cells via an enhancer that is located in intron 1 of the Dhh gene. Sox10 binds this enhancer in monomeric form via several sites. Mutation of these sites abolishes both Schwann-cell-specific activity and Sox10 responsiveness in vitro and in transgenic mouse embryos. This argues that Sox10 activates Dhh expression by direct binding to the enhancer and by increasing Dhh levels promotes formation of the perineurial sheath. This represents the first mechanism for a non-cell-autonomous function of Sox10 during peripheral nerve development. © 2012 the authors.
UnivIS-Import:2015-03-09:Pub.2012.med.IB.LPCIPDBI.desert

Dual specificity phosphatase 15 regulates Erk activation in Schwann cells - Rodriguez-Molina, Jose F.; Lopez-Anido, Camila; Ma, Ki H.; Zhang, Chongyu; Olson, Tyler; Weider, Matthias; Muth, Katharina; Svaren, John (Journal of Neurochemistry, 2017)
Schwann cells and oligodendrocytes are the myelinating cells of the peripheral and central nervous system, respectively. Despite having different myelin components and different transcription factors driving their terminal differentiation there are shared molecular mechanisms between the two. Sox10 is one common transcription factor required for several steps in development of myelinating glia. However, other factors are divergent as Schwann cells need the transcription factor early growth response 2/Krox20 and oligodendrocytes require Myrf. Likewise, some signaling pathways, like the Erk1/2 kinases, are necessary in both cell types for proper myelination. Nonetheless, the molecular mechanisms that control this shared signaling pathway in myelinating cells remain only partially characterized. The hypothesis of this study is that signaling pathways that are similarly regulated in both Schwann cells and oligodendrocytes play central roles in coordinating the differentiation of myelinating glia. To address this hypothesis, we have used genome-wide binding data to identify a relatively small set of genes that are similarly regulated by Sox10 in myelinating glia. We chose one such gene encoding Dual specificity phosphatase 15 (Dusp15) for further analysis in Schwann cell signaling. RNA interference and gene deletion by genome editing in cultured RT4 and primary Schwann cells showed Dusp15 is necessary for full activation of Erk1/2 phosphorylation. In addition, we show that Dusp15 represses expression of several myelin genes, including myelin basic protein. The data shown here support a mechanism by which early growth response 2 activates myelin genes, but also induces a negative feedback loop through Dusp15 to limit over-expression of myelin genes.
EVALuna2:33487

Elevated in vivo levels of a single transcription factor directly convert satellite glia into oligodendrocyte-like cells - Weider, Matthias; Wegener, Amelie; Schmitt-Engel, Christian; Küspert, Melanie; Hillgaertner, Simone; Boesl, Michael R.; Hermans-Borgmeyer, Irm; Nait-Oumesmar, Brahim; Wegner, Michael (PLoS Genetics, 2015)
Oligodendrocytes are the myelinating glia of the central nervous system and ensure rapid saltatory conduction. Shortage or loss of these cells leads to severe malfunctions as observed in human leukodystrophies and multiple sclerosis, and their replenishment by reprogramming or cell conversion strategies is an important research aim. Using a transgenic approach we increased levels of the transcription factor Sox10 throughout the mouse embryo and thereby prompted Fabp7-positive glial cells in dorsal root ganglia of the peripheral nervous system to convert into cells with oligodendrocyte characteristics including myelin gene expression. These rarely studied and poorly characterized satellite glia did not go through a classic oligodendrocyte precursor cell stage. Instead, Sox10 directly induced key elements of the regulatory network of differentiating oligodendrocytes, including Olig2, Olig1, Nkx2.2 and Myrf. An upstream enhancer mediated the direct induction of the Olig2 gene. Unlike Sox10, Olig2 was not capable of generating oligodendrocyte-like cells in dorsal root ganglia. Our findings provide proof-of-concept that Sox10 can convert conducive cells into oligodendrocyte-like cells in vivo and delineates options for future therapeutic strategie
EVALuna2:4978

Formation of the node of Ranvier by Schwann cells is under control of transcription factor Sox10 - Saur, Anna-Lena; Fröb, Franziska; Weider, Matthias; Wegner, Michael (Glia, 2021)
The transcription factor Sox10 is an essential regulator of genes that code for structural components of the myelin sheath and for lipid metabolic enzymes in both types of myelinating glia in the central and peripheral nervous systems. In an attempt to characterize additional Sox10 target genes in Schwann cells, we identified in this study a strong influence of Sox10 on the expression of genes associated with adhesion in the MSC80 Schwann cell line. These included the genes for Gliomedin, Neuronal cell adhesion molecule and Neurofascin that together constitute essential Schwann cell contributions to paranode and node of Ranvier. Using bioinformatics and molecular biology techniques we provide evidence that Sox10 directly activates these genes by binding to conserved regulatory regions. For activation, Sox10 cooperates with Krox20, a transcription factor previously identified as the central regulator of Schwann cell myelination. Both the activating function of Sox10 as well as its cooperation with Krox20 were confirmed in vivo. We conclude that the employment of Sox10 and Krox20 as regulators of structural myelin sheath components and genes associated with the node of Ranvier is one way of ensuring a biologically meaningful coordinated formation of both structures during peripheral myelination.
CRIS-Team Scopus Importer:2021-03-05
Keywords: glia; HMG; Krox; node of Ranvier; Schwann cell; Sox

Gain of Olig2 function in oligodendrocyte progenitors promotes remyelination - Wegener, Amelie; Deboux, Cyrille; Bachelin, Corinne; Frah, Magali; Kerninon, Christophe; Seilhean, Danielle; Weider, Matthias; Wegner, Michael; Nait-Oumesmar, Brahim (Brain, 2015)
The basic helix-loop-helix transcription factor Olig2 is a key determinant for the specification of neural precursor cells into oligodendrocyte progenitor cells. However, the functional role of Olig2 in oligodendrocyte migration and differentiation remains elusive both during developmental myelination and under demyelinating conditions of the adult central nervous system. To decipher Olig2 functions, we generated transgenic mice (TetOlig2:Sox10(rtTA/+)) overexpressing Olig2 in Sox10(+) oligodendroglial cells in a doxycycline inducible manner. We show that Olig2 overexpression increases the generation of differentiated oligodendrocytes, leading to precocious myelination of the central nervous system. Unexpectedly, we found that gain of Olig2 function in oligodendrocyte progenitor cells enhances their migration rate. To determine whether Olig2 overexpression in adult oligodendrocyte progenitor cells promotes oligodendrocyte regeneration for myelin repair, we induced lysophosphatidylcholine demyelination in the corpus callosum of TetOlig2:Sox10(rtTA/+) and control mice. We found that Olig2 overexpression enhanced oligodendrocyte progenitor cell differentiation and remyelination. To assess the relevance of these findings in demyelinating diseases, we also examined OLIG2 expression in multiple sclerosis lesions. We demonstrate that OLIG2 displays a differential expression pattern in multiple sclerosis lesions that correlates with lesion activity. Strikingly, OLIG2 was predominantly detected in NOGO-A(+) (now known as RTN4-A) maturing oligodendrocytes, which prevailed in active lesion borders, rather than chronic silent and shadow plaques. Taken together, our data provide proof of principle indicating that OLIG2 overexpression in oligodendrocyte progenitor cells might be a possible therapeutic mechanism for enhancing myelin repair.
EVALuna2:4980

Halitosis in Oral and Maxillofacial Surgery Patients-a Pilot Study - Willershausen, Ines; Krautkremer, Franziska; Sagheb, Kawe; Weider, Matthias; Weusmann, Jens; Mittermeier, Fabienna; Erhard, Julia; Sagheb, Keyvan; Gölz, Lina; Walter, Christian (Clinical Laboratory, 2021)
Background: Halitosis is a relatively inhomogeneous pathology with an extremely high prevalence in the population. Potential risk factors for bad breath include bacterial decomposition of organic material as well as numerous general and systemic diseases. The aim of the present study was to analyze whether certain subgroups of oral and maxillofacial surgery patients have a higher risk of halitosis. Further the impact of halitosis on the patient's quality of life was ascertained.
CRIS-Team WoS Importer:2021-12-10

Impact of the microRNA family miR-204/-211 on the oligodendroglial gene regulatory network - Wittstatt, Jan; Weider, Matthias; Reiprich, Simone; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Influence of Natural Killer Cells and Natural Killer T Cells on Periodontal Disease: A Systematic Review of the Current Literature - Seidel, Andreas; Seidel, Corinna Lesley; Weider, Matthias; Junker, Ruediger; Gölz, Lina; Schmetzer, Helga (International Journal of Molecular Sciences, 2020)
Natural killer (NK) cells, as members of the innate immune system, and natural killer T (NKT) cells, bridging innate and adaptive immunity, play a prominent role in chronic inflammatory diseases and cancerogenesis, yet have scarcely been examined in oral diseases. Therefore, systematic research on the latest literature focusing on NK/NKT cell-mediated mechanisms in periodontal disease, including the time period 1988-2020, was carried out in MEDLINE (PubMed) using a predetermined search strategy, with a final selection of 25 studies. The results showed that NK cells tend to have rather proinflammatory influences via cytokine production, cytotoxic effects, dendritic-cell-crosstalk, and autoimmune reactions, while contrarily, NKT cell-mediated mechanisms were proinflammatory and immunoregulatory, ranging from protective effects via B-cell-regulation, specific antibody production, and the suppression of autoimmunity to destructive effects via cytokine production, dendritic-cell-crosstalk, and T-/B-cell interactions. Since NK cells seem to have a proinflammatory role in periodontitis, further research should focus on the proinflammatory and immunoregulatory properties of NKT cells in order to create, in addition to antibacterial strategies in dental inflammatory disease, novel anti-inflammatory therapeutic approaches modulating host immunity towards dental health.
CRIS-Team WoS Importer:2021-01-22

Influence of probiotics on the periodontium, the oral microbiota and the immune response during orthodontic treatment in adolescent and adult patients (ProMB Trial): study protocol for a prospective, double-blind, controlled, randomized clinical trial - Seidel, Corinna Lesley; Gerlach, Roman; Weider, Matthias; Woelfel, Theresa; Schwarz, Vincent; Stroebel, Armin; Schmetzer, Helga; Bogdan, Christian; Gölz, Lina (BMC Oral Health, 2022)
Background Orthodontic treatment with fixed appliances is often necessary to correct malocclusions in adolescence or adulthood. However, oral hygiene is complicated by appliances, and prior studies indicate that they may trigger oral inflammation and dysbiosis of the oral microbiota, especially during the first 3 months after insertion, and, thus, may present a risk for inflammatory oral diseases. In recent periodontal therapeutic studies, probiotics have been applied to improve clinical parameters and reduce local inflammation. However, limited knowledge exists concerning the effects of probiotics in orthodontics. Therefore, the aim of our study is to evaluate the impact of probiotics during orthodontic treatment. Methods This study is a monocentric, randomized, double blind, controlled clinical study to investigate the effectiveness of daily adjuvant use of Limosilactobacillus reuteri (Prodentis (R)-lozenges, DSM 17938, ATCC PTA 5289) versus control lozenges during the first three months of orthodontic treatment with fixed appliances. Following power analysis, a total of 34 adolescent patients (age 12-17) and 34 adult patients (18 years and older) undergoing orthodontic treatment at the University Hospital Erlangen will be assigned into 2 parallel groups using a randomization plan for each age group. The primary outcome measure is the change of the gingival index after 4 weeks. Secondary outcomes include the probing pocket depth, the modified plaque index, the composition of the oral microbiota, the local cytokine expression and-only for adults-serum cytokine levels and the frequencies of cells of the innate and adaptive immune system in peripheral blood. Discussion Preventive strategies in everyday orthodontic practice include oral hygiene instructions and regular dental cleaning. Innovative methods, like adjuvant use of oral probiotics, are missing. The aim of this study is to analyse, whether probiotics can improve clinical parameters, reduce inflammation and prevent dysbiosis of the oral microbiota during orthodontic treatment. If successful, this study will provide the basis for a new strategy of prophylaxis of oral dysbiosis-related diseases during treatment with fixed appliances.
CRIS-Team WoS Importer:2022-05-13
Keywords: Probiotics; Lactobacillus reuteri; Limosilactobacillus reuteri; Oral microbiota; Cytokines; Inflammation; Orthodontic treatment; Oral health; Prevention; Study protocol

MicroRNA miR-204 regulates proliferation and differentiation of oligodendroglia in culture - Wittstatt, Jan; Weider, Matthias; Wegner, Michael; Reiprich, Simone (Glia, 2020)
Oligodendrocytes wrap and physically shield axons of the central nervous system with myelin sheaths, resulting in rapid signal transduction and accurate neuronal function. The complex oligodendroglial development from immature oligodendrocyte precursor cells (OPCs) to myelinating oligodendrocytes (OLs) is profoundly dependent on the activity of transcription factors of the Sox protein family. Target genes of the crucial regulator Sox10 have recently been expanded to microRNAs. Here, we report miR-204 as a novel transcriptional target of Sox10. Regulatory regions of miR-204 show responsiveness to and binding of Sox10 in reporter gene assays and electromobility shift assays. Once expressed, miR-204 inhibits OPC proliferation and facilitates differentiation into OLs in the presence of Sox10 as evident from overexpression in primary rat and mouse oligodendroglial cultures. Phenotypes are at least in part caused by miR-204-dependent repression of the pro-proliferative Ccnd2 and the differentiation inhibiting Sox4. These findings argue that the transcriptional activator Sox10 forces oligodendroglial cells to exit the cell cycle and start differentiation by gene inhibition via miR-204 induction.
CRIS-Team Scopus Importer:2020-03-27
Keywords: glia; microRNA; myelination; proliferation; regulatory network; Sox proteins

Myrf as a molecular switch for target gene selection of Sox10 during oligodendroglial development - Aprato, Jessica; Küspert, Melanie; Weider, Matthias; Fröb, Franziska; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Myrf guides target gene selection of transcription factor Sox10 during oligodendroglial development - Aprato, Jessica; Sock, Elisabeth; Weider, Matthias; Elsesser, Olga; Fröb, Franziska; Wegner, Michael (Nucleic Acids Research, 2020)
Oligodendrocytes generate myelin in the vertebrate central nervous system and thus ensure rapid propagation of neuronal activity. Their development is controlled by a network of transcription factors that function as determinants of cell identity or as temporally restricted stage-specific regulators. The continuously expressed Sox10 and Myrf, a factor induced during late development, are particularly important for terminal differentiation. How these factors function together mechanistically and influence each other, is not well understood. Here we show that Myrf not only cooperates with Sox10 during the induction of genes required for differentiation and myelin formation. Myrf also inhibits the activity of Sox10 on genes that are essential during earlier phases of oligodendroglial development. By characterization of the exact DNA-binding requirements of Myrf, we furthermore show that cooperative activation is a consequence of joint binding of Sox10 and Myrf to the same regulatory regions. In contrast, inhibition of Sox10-dependent gene activation occurs on genes that lack Myrf binding sites and likely involves physical interaction between Myrf and Sox10 followed by sequestration. These two opposite activities allow Myrf to redirect Sox10 from genes that it activates in oligodendrocyte precursor cells to genes that need to be induced during terminal differentiation.
CRIS-Team WoS Importer:2020-03-10

Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning. - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
Oligodendrocytes produce myelin for rapid transmission and saltatory conduction of action potentials in the vertebrate central nervous system. Activation of the myelination program requires several transcription factors including Sox10, Olig2, and Nkx2.2. Functional interactions among them are poorly understood and important components of the regulatory network are still unknown. Here, we identify Nfat proteins as Sox10 targets and regulators of oligodendroglial differentiation in rodents and humans. Overall levels and nuclear fraction increase during differentiation. Inhibition of Nfat activity impedes oligodendrocyte differentiation in vitro and in vivo. On a molecular level, Nfat proteins cooperate with Sox10 to relieve reciprocal repression of Olig2 and Nkx2.2 as precondition for oligodendroglial differentiation and myelination. As Nfat activity depends on calcium-dependent activation of calcineurin signaling, regulatory network and oligodendroglial differentiation become sensitive to calcium signals. NFAT proteins are also detected in human oligodendrocytes, downregulated in active multiple sclerosis lesions and thus likely relevant in demyelinating disease.
UnivIS-Import:2018-09-11:Pub.2018.med.IB.LPCIPDBI.nfatca

Nkx2.2 is a direct target gene of Sox10 in oligodendroglia - Weider, Matthias; Schmitt, Christian; Hillgärtner, Simone; Wegner, Michael (2017)
EVALuna2:33484

Orofacial clefts alter early life oral microbiome maturation towards higher levels of potentially pathogenic species: A prospective observational study - Seidel, Corinna Lesley; Strobel, Karin; Weider, Matthias; Tschaftari, Marco; Unertl, Christoph; Willershausen, Ines; Weber, Manuel; Hörning, André; Morhart, Patrick; Schneider, Michael; Beckmann, Matthias; Bogdan, Christian; et al. (Journal of Oral Microbiology, 2023)
Orofacial clefts (OFC) present different phenotypes with a postnatal challenge for oral microbiota development. In order to investigate the impact of OFC on oral microbiota, smear samples from 15 neonates with OFC and 17 neonates without OFC were collected from two oral niches (tongue, cheek) at two time points, i.e. after birth (T0: Ø3d OFC group; Ø2d control group) and 4–5 weeks later (T1: Ø32d OFC group; Ø31d control group). Subsequently, the samples were analyzed using next-generation sequencing. We detected a significant increase of alpha diversity and anaerobic and Gram-negative species from T0 to T1 in both groups. Further, we found that at T1 OFC neonates presented a significantly lower alpha diversity (lowest values for high cleft severity) and significantly higher levels of Enterobacteriaceae (Citrobacter, Enterobacter, Escherichia-Shigella, Klebsiella), Enterococcus, Bifidobacterium, Corynebacterium, Lactocaseibacillus, Staphylococcus, Acinetobacter and Lawsonella compared to controls. Notably, neonates with unilateral and bilateral cleft lip and palate (UCLP/BCLP) presented similarities in beta diversity and a mixture with skin microbiota. However, significant differences were seen in neonates with cleft palate only compared to UCLP/BCLP with higher levels of anaerobic species. Our findings revealed an influence of OFC as well as cleft phenotype and severity on postnatal oral microbiota maturation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: early life dysbiosis; microbiome maturation; neonates; oral microbiome; Orofacial clefts

Orofacial clefts lead to increased pro-inflammatory cytokine levels on neonatal oral mucosa - Seidel, Corinna Lesley; Percivalle, Elena; Tschaftari, Marco; Weider, Matthias; Strobel, Karin; Willershausen, Ines; Unertl, Christoph; Schmetzer, Helga M.; Weber, Manuel; Schneider, Michael; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Immunology, 2022)
Orofacial clefts (OFC) are frequent congenital malformations characterized by insufficient separation of oral and nasal cavities and require presurgical infant orthopedics and surgical interventions within the first year of life. Wound healing disorders and higher prevalence of gingivitis and plaque levels are well-known challenges in treatment of children with OFC. However, oral inflammatory mediators were not investigated after birth using non-invasive sampling methods so far. In order to investigate the impact of OFC on oral cytokine levels, we collected tongue smear samples from 15 neonates with OFC and 17 control neonates at two time points (T), T0 at first consultation after birth, and T1, 4 to 5 weeks later. The samples were analyzed using multiplex immunoassay. Overall, we found significantly increased cytokine levels (TNF, IL-1β/-2/-6/-8/-10) in tongue smear samples from neonates with OFC compared to controls, especially at T0. The increase was even more pronounced in neonates with a higher cleft severity. Further, we detected a significant positive correlation between cleft severity score and distinct pro-inflammatory mediators (GM-CSF, IL-1β, IL-6, IL-8) at T0. Further, we found that breast-milk (bottle) feeding was associated with lower levels of pro-inflammatory cytokines (IL-6/-8) in neonates with OFC compared to formula-fed neonates. Our study demonstrated that neonates with OFC, especially with high cleft severity, are characterized by markedly increased inflammatory mediators in tongue smear samples within the first weeks of life potentially presenting a risk for oral inflammatory diseases. Therefore, an inflammatory monitoring of neonates with (severe) OFC and the encouragement of mother to breast-milk (bottle) feed might be advisable after birth and/or prior to cleft surgery.
CRIS-Team Scopus Importer:2022-12-16
Keywords: cleft lip and palate; cytokines; mucosal homeostasis; mucosal immunity; neonates; oral; oral inflammation; orofacial clefts

Publisher Correction: Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
The originally published version of this Article omitted Tanja Kuhlmann and Michael Wegner as jointly supervising authors. This has now been corrected in both the PDF and HTML versions of the Article.
EVALuna2:35744

Sox9 overexpression exerts multiple stage-dependent effects on mouse spinal cord development - Vogel, Julia; Weider, Matthias; Engler, Lisa; Hillgärtner, Simone; Schmitt, Christian; Hermans-Borgmeyer, Irm; Wegner, Michael (Glia, 2019)
The high-mobility-group (HMG)-domain protein Sox9 is one of few transcription factors implicated in gliogenesis in the vertebrate central nervous system. To further study the role of Sox9 in early spinal cord development, we generated a mouse that allows expression of Sox9 in a temporally and spatially controlled manner. Using this mouse, we show that premature Sox9 expression in neural precursor cells disrupted the neuroepithelium of the ventricular zone. Sox9 also compromised development and survival of neuronal precursors and neurons. Additionally, we observed in these mice substantial increases in oligodendroglial and astroglial cells. Reversing the normal order of appearance of essential transcriptional regulators during oligodendrogenesis, Sox10 preceded Olig2. Our study reinforces the notion that Sox9 has a strong gliogenic activity. It also argues that Sox9 expression has to be tightly controlled to prevent negative effects on early spinal cord structure and neuronal development.
CRIS-Team WoS Importer:2019-11-26

Sox9-overexpression promotes gliogenesis at the expense of neurogenesis in the embryonic mouse spinal cord - Vogel, Julia; Weider, Matthias; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Sox appeal - Sox10 attracts epigenetic and transcriptional regulators in myelinating glia - Weider, Matthias; Reiprich, Simone; Wegner, Michael (Biological Chemistry, 2013)
Sox10 belongs to the Sox family of high-mobility group-box transcription factors. It fulfils widespread and essential functions in myelinating glia at multiple stages of development such as glial specification, survival and terminal differentiation. To a large extent, these diverse activities can be attributed to its capacity to interact with different transcription factors in distinct regulatory networks. Beyond transcription factors, an increasing number of interaction partners are emerging with alternative impact on gene expression. These include components of the mediator complex, the Brahma-associated factor complex and histone deacetylases. Here, we discuss interactions with functional relevance in myelinating glia and link Sox10 function in these cells not only to gene transcription, but also to epigenetics and chromatin remodeling.
EVALuna2:4944

SoxE factors: Transcriptional regulators of neural differentiation and nervous system development. - Weider, Matthias; Wegner, Michael (Seminars in Cell & Developmental Biology, 2017)
Sox8, Sox9 and Sox10 represent the three vertebrate members of the SoxE subclass of high-mobility-group domain containing Sox transcription factors. They play important roles in the peripheral and central nervous systems as regulators of stemness, specification, survival, lineage progression, glial differentiation and homeostasis. Functions are frequently overlapping, but sometimes antagonistic. SoxE proteins dynamically interact with transcriptional regulators, chromatin changing complexes and components of the transcriptional machinery. By establishing regulatory circuits with other transcription factors and microRNAs, SoxE proteins perform divergent functions in several cell lineages of the vertebrate nervous system, and at different developmental stages in the same cell lineage. The underlying molecular mechanisms are the topic of this review.<br
EVALuna2:33486
Keywords: Brain; Glia; Neural crest; Oligodendrocyte; Schwann cell; Transcriptional network

The Dual-specificity phosphatase Dusp15 is regulated by Sox10 and Myrf in Myelinating Oligodendrocytes - Muth, Katharina; Piefke, Sandra; Weider, Matthias; Sock, Elisabeth; Hermans-Borgmeyer, Irm; Wegner, Michael; Küspert, Melanie (Glia, 2016)
Differentiation of oligodendrocytes and myelin production in the vertebrate central nervous system require highly concerted changes in gene expression. The transcription factors Sox10 and Myrf are both central to this process and jointly regulate expression of myelin genes. Here we show that Sox10 and Myrf also cooperate in the activation of the gene coding for the dual specificity protein phosphatase Dusp15 (also known as VHY) during this process. Activation is mediated by the Dusp15 promoter, which is also sufficient to drive oligodendroglial gene expression in vivo. It contains both a functional Sox10 and a functional Myrf binding site. Whereas Sox10 binds as a monomer, Myrf binds as a trimer. Available data furthermore indicate that cooperative activation is not a function of facilitated binding, but occurs at a later step of the activation process. shRNA-mediated knockdown of Dusp15 reduced expression of early and late differentiation markers in CG4 and primary oligodendroglial cells, whereas Dusp15 overexpression increased it transiently. This argues that Dusp15 is not only a joint target of Sox10 and Myrf in oligodendrocytes but may also mediate some of their effects during oligodendrocyte differentiation and myelin formation. GLIA 2016;64:2120-2132.
EVALuna2:4997

The Tip60/Ep400 chromatin remodeling complex impacts basic cellular functions in cranial neural crest-derived tissue during early orofacial development - Gehlen-Breitbach, Sebastian; Schmid, Theresa; Fröb, Franziska; Rodrian, Gabriele; Weider, Matthias; Wegner, Michael; Gölz, Lina (International Journal of Oral Science, 2023)
The cranial neural crest plays a fundamental role in orofacial development and morphogenesis. Accordingly, mutations with impact on the cranial neural crest and its development lead to orofacial malformations such as cleft lip and palate. As a pluripotent and dynamic cell population, the cranial neural crest undergoes vast transcriptional and epigenomic alterations throughout the formation of facial structures pointing to an essential role of factors regulating chromatin state or transcription levels. Using CRISPR/Cas9-guided genome editing and conditional mutagenesis in the mouse, we here show that inactivation of Kat5 or Ep400 as the two essential enzymatic subunits of the Tip60/Ep400 chromatin remodeling complex severely affects carbohydrate and amino acid metabolism in cranial neural crest cells. The resulting decrease in protein synthesis, proliferation and survival leads to a drastic reduction of cranial neural crest cells early in fetal development and a loss of most facial structures in the absence of either protein. Following heterozygous loss of Kat5 in neural crest cells palatogenesis was impaired. These findings point to a decisive role of the Tip60/Ep400 chromatin remodeling complex in facial morphogenesis and lead us to conclude that the orofacial clefting observed in patients with heterozygous KAT5 missense mutations is at least in part due to disturbances in the cranial neural crest.
CRIS-Team Scopus Importer:2023-04-21

The transcription factor Sox10 is an essential determinant of branching morphogenesis and involution in the mouse mammary gland - Mertelmeyer, Svenja; Weider, Matthias; Baroti, Tina; Reiprich, Simone; Fröb, Franziska; Stolt, Claus; Wagner, Kay Uwe; Wegner, Michael (Scientific Reports, 2020)
The high mobility group-domain containing transcription factor Sox10 is an essential regulator of developmental processes and homeostasis in the neural crest, several neural crest-derived lineages and myelinating glia. Recent studies have also implicated Sox10 as an important factor in mammary stem and precursor cells. Here we employ a series of mouse mutants with constitutive and conditional Sox10 deficiencies to show that Sox10 has multiple functions in the developing mammary gland. While there is no indication for a requirement of Sox10 in the specification of the mammary placode or descending mammary bud, it is essential for both the prenatal hormone-independent as well as the pubertal hormone-dependent branching of the mammary epithelium and for proper alveologenesis during pregnancy. It furthermore acts in a dosage-dependent manner. Sox10 also plays a role during the involution process at the end of the lactation period. Whereas its effect on epithelial branching and alveologenesis are likely causally related to its function in mammary stem and precursor cells, this is not the case for its function during involution where Sox10 seems to work at least in part through regulation of the miR-424(322)/503 cluster.
CRIS-Team Scopus Importer:2020-10-30

Transcription factor Sox10 induces the microRNAs miR-335, miR-338 and miR-155 to ensure correct timing of oligodendrocyte development - Küspert, Melanie; Reiprich, Simone; Cantone, Martina; Weider, Matthias; Baroti, Tina; Wittstatt, Jan; Vera, Julio; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Transcription factor Sox10 regulates oligodendroglial Sox9 levels via microRNAs. - Reiprich, Simone; Cantone, Martina; Weider, Matthias; Baroti, Tina; Wittstatt, Jan; Schmitt, Christian; Küspert, Melanie; Vera, Julio; Wegner, Michael (Glia, 2017)
During development of myelin-forming oligodendrocytes in the central nervous system the two closely related transcription factors Sox9 and Sox10 play essential roles that are partly shared and partly unique. Whereas Sox9 primarily functions during oligodendroglial specification, Sox10 is uniquely required to induce terminal differentiation and myelination. During this process, Sox10 protein levels rise substantially. As this coincides with a reciprocal decrease in Sox9, we postulated that Sox10 influences Sox9 amounts in differentiating oligodendrocytes. Here we show that Sox9 levels are indeed inversely coupled to Sox10 levels such that Sox10 deletion in oligodendroglial cells evokes a reciprocal increase in Sox9. We furthermore provide evidence that this coupling involves upregulation of microRNAs miR335 and miR338 as direct transcriptional targets of Sox10. The two microRNAs in turn recognize the 3′-UTR of Sox9 mRNA and may thereby reduce Sox9 protein levels posttranscriptionally in oligodendroglial cells. Such a mechanism may enable oligodendroglial cells to adapt the ratio of both related Sox proteins in a manner required for successful lineage progression and differentiation. Mathematical modeling furthermore shows that the identified regulatory circuit has the potential to convert a transient stimulus into an irreversible switch of cellular properties and may thus contribute to terminal differentiation of oligodendrocytes.
EVALuna2:33479
Keywords: glia; HMG; miR338; oligodendrocyte; Sox